The Influence of Transformational Leadership, Transactional Leadership and Lecturers’ Competence on the Performance of Naval Staff and Command School Lecturers Mediated by Motivation - Lazuardi, Rudi; Suharjo, Bambang (Journal of Industrial Engineering & Management Research, 2023)
The purpose of this study was to analyze the performance of Seskoal lecturers by observing the influence of the aspects of Transactional Leadership, Transactional Leadership, Competence, and Motivation of the lecturers as mediating variables. The research was conducted within the scope of the Naval Staff and Command School with 105 respondents consisting of Seskoal lecturers and structural officials involved in teaching, training, and nurturing activities. The data obtained were analyzed using Structural Equation Model-Partial Least Square (SEM-PLS) software. The independent variables Transformational Leadership and Transactional Leadership were found to have no direct effect on performance. Instead, the independent variables Competence and Motivation positively and significantly affected performance. This argument is due to the fact that the performance dimension in the form of the Tridarma of Higher Education has yet to be widely understood. The working period of lecturers is generally short, so the impact of the transformation has yet to be felt. It is also very rare for transactions to occur in this performance. Variable influence. The effect of the independent variable Transformational Leadership also has no positive and significant effect on motivation as the dependent variable, whereas Transactional Leadership and Competence have a positive and significant effect on Motivation. This result shows that transactions will increase lecturers' motivation, and lecturers with high competence will automatically increase their motivation. Interestingly, the indirect effect, where motivation acts as an intervening variable, shows that there is no effect of Transformational Leadership on Performance through motivation. However, vice versa for the variables Transactional Leadership and Competence affect Performance through Motivation. This result shows that the effect of the transformation has not been felt directly or indirectly as explained otherwise, for transactions will increase motivation which indirectly increases performance and competence.